ON THE ISSUE OF SCIENTIFIC AND TECHNOLOGICAL PROGRESS, THE LABOR MARKET AND TECHNOLOGICAL BACKWARDNESS OF RUSSIA - I. E. Zolin (Вестник университета)
The complex process of adaptation of modern society to the new conditions of development associated with the introduction of the latest achievements of scientific and technological progress has been examined. In this regard, the features of scientific and technological progress, its impact on the labor market, as well as the problems of technological backwardness of Russia have been analyzed. As an empirical base, the authors have used some results of the sociological study “Problems and prospects of the Russian labor market”, conducted by the author in Nizhny Novgorod in 2018 using the method of in-depth expert interviews. The study has identified 26 storylines, one of which, related directly to the views of experts on scientific and technological progress. The characteristic of this storyline has been presented in the article.